Adverbs on the move: investigating publisher application of corpus research on recent language change to ELT coursebook development. Issue 1 (April 2022) - Curry, Niall; Love, Robbie; Goodman, Olivia
Abstract : While the role of corpus linguistics (cl ) in language teaching and learning continues to evolve, its use in the language teaching industry remains somewhat unclear. The specific ways in which elt publishers use cl research to inform materials development are under-studied, meaning that it is not known whether cl is being used by publishers to its full potential. This study investigates the use of cl research by a major international elt publisher by conducting research into recent change in adverbs in casual spoken British English and sharing the findings with editors from the publisher. Through our analysis, we find evidence of major recent changes in the use of frequent adverbs. Following the corpus analysis, we conducted in-depth interviews with the editors and a review of the materials they subsequently produced using the corpus findings. In so doing, we find some evidence of effective use of corpora in materials development but reveal limitations in current corpus research which prevent editors from employing cl research more effectively.